Developmental Coordination Disorder in Chinese Children Is Correlated With Cognitive Deficits - Ke, Li; Duan, Wen; Xue, Ye; Wang, Yun (Frontiers in Psychiatry, 2019)
Cognitive deficits have been commonly observed in children with developmental coordination disorder (DCD), including memory, attention, and executive function difficulties. The present study evaluates the specific cognitive deficits in Chinese children with DCD through a number of tests. A total of 401 children aged 7 to 10 years old from primary schools in Guangdong Province, China, participated in this study. Using the guidelines of the Movement Assessment Battery for Children (“Movement ABC-2”), a measurement tool of motor function ability, the children were divided into a DCD group, a group identified as being at risk of DCD, and a normal control group. The results of our analysis revealed that children’s overall motor abilities could predict their overall cognitive ability, reaction time, memory, and attention. The performance of the DCD children was worse than that of the other two groups in terms of reaction time. The DCD group also returned lower scores for executive function than did the normal control group. Regression analysis showed that the cognitive deficits in children with DCD centers mainly on poor executive function rather than attention and memory issues. These findings provide preliminary results regarding cognitive deficits in Chinese children with DCD and have potential applications for the diagnosis and treatment of the disorder.